Organisational capability in internalising quality culture in higher institution - Muhammad Ibrahim, Bello; Ibrahim, Mohd Burhan; Mohammed Waziri, Bularafa (International Institute for Science, Technology & Education (IISTE), 2015)
The study examines the influence of leadership roles related to organisational capability consisting of directing setting, strategic and organisational process, alignment, intervention and strategic capability on depending variable internalising quality culture in IIUM. The study used 100 samples consisting of lecturers, non-academic staff and students drew through purposive sampling in Gombak campus. The study employed descriptive and multiple regression analysis (MRA) in analysing the data. The results revealed that predictors directing setting, strategic and organisational processes and strategic capabilities significantly influenced internalising quality culture in IIUM.